A Formação no Programa de Trabalho Educativo da FIA/RJ: possibilidades e limites da experiência - Lessa, Simone Eliza do Carmo (2004)
The present study analyzes the formation provided by the Educational Program of Work organized by the FIA/RJ - Foundation for Infancy and Adolescence of Rio de Janeiro. For that, we situate our object in the context of the capitalism in the1990’s, especially concerning the organization of the world field, where we focus on the weakening of the fordist model and the Welfare State, the precarious work conditions and social protection conquered by the workers, the weakening of the wage relations, and also the growth of the new forms of labour force management. In addition, we discuss the politics and handling of the infancy and the poor youth historically. We do so by analyzing the integration of the PTE/FIA in this context. We emphasize the 1930's, when the social question becomes a systematic matter of intervention of the Brazilian State, which arrived in the 1990's, with the advent of the ECA. Then, we discuss the central category in our analysis: the category of formation. This category is marked by contradictions that reveal its diverse appropriation by the capital based on a perspective interested in the improvement of the human potential. Bearing these possibilities in mind, we discuss the formation in the polyvalence or polytechnical education point of view and we point out the last as the nearest formative action implemented in the PTE. Finally, we present the empirical facts in the research, giving details taken from the interviews and from our own professional experience and aspects that aim at the formation in the Program. Among the most important are: the training in service, the courses and workshops, and the relation between supervisor and scholarship holders. All in all, it is the idea of that the predominant model of formation which leads us to “polivalência”, but there it assumes an aspect which is even more impoverished because it is built based on simple work. This chart is not certainly separate from a bigger project of formation that there is in the LDB and in the basic level qualification processes in their legal structure. They turn to the young poor workers who will take up the simplest occupations. On the other hand, when the experience happens through the development of less simple activities associated with school reinforcement activities, the courses and workshops -- what do not only have to answer the demands of the work, but to take care of to the necessities and interests of the scholarship holders -- the possibilities of a formation less conforming and capable to enlarge youth’s horizons of expectations, happen.